Synthesis and characterisation of aluminium composite with graphene oxide reinforcement - Fuhaid, Mutlag Shafi; Murali, R V; Maleque, Md. Abdul; Krishnan, P K; Abd. Rahman, Mohamed (IOP Publishing, 2021)
Aluminium matrix composites (AMCs) find a broader spectrum of applications inconsiderable number of industries globally as AMCs possess excellent mechanical properties at lower mass density. Due to many advantages, researchers continue to find a new generation of materials that offer designers many benefits in converting traditional materials into commercial and industrial materials to use low cost or waste materials as reinforcing phase while producing AMCs. In this research work, Graphene Oxide (GO) is used as a reinforcing phase in the LM6 aluminium matrix, and this paper attempts to lay more emphasis on synthesis and characterization of LM6 matrix and GO particulates and LM6/GO composites as a whole. A modified stir casting process was employed to develop the above composite material. The composite test pieces were subject to physical and mechanical tests, i.e., density, hardness, tensile, and impact. Microanalysis methods such as SEM and XRD analysis were also performed on the composite specimens to analyze the feasibility and suitability of the materials for further research work (friction welding of composites) being pursued by the authors. The results and insights drawn from the comprehensive laboratory analysis demonstrated that the LM6/GO composite could be successfully used as alternative materials replacing metal and alloys. Furthermore, the composite can be easily subject to the welding process resulting in quality welded joints and assemblies.